Membangun Makna Teologis Gotong Royong dalam Memperkuat Kebhinekaan - Deasy Elisabeth Wattimena-Kalalo (Sekolah Tinggi Teologi Torsina Surakarta, 2020)
This article discusses the form of dialogue based on social relations as an effort to approach radical Islamic groups to maintain diversity in Indonesia country. It is a manifestation of the spirit of postmodern plurality in the context of the theology of religions. The aim of the problem of this research is how to maintain diversity with radical groups in the context of postmodern plurality and how connected this spirit is to the ecumenical procession. The author uses a literature study to analyze it. The spirit of postmodern plurality promotes the principle of mutual cooperation which mediates Christian groups for dialogue based on social relations with radical groups. This encouragement to build relationships with groups that keep their distance from Christianity requires an inherent cultural approach between the two and a spirit that unites as a nation. That way, dialogue with radical groups is not a necessity but a possibility to maintain diversity. AbstrakArtikel ini membahas tentang bentuk dialog berbasis relasi sosial sebagai upaya mendekati kelompok Islam Radikal untuk menjaga kebhinekaan sebagai perwujudan semangat pluralitas postmodern dalam konteks berteologi agama-agama. Rumusan masalah penelitian ini adalah bagaimana menjaga kebhinekaan bersama kelompok radikal dalam konteks pluralitas postmodern dan seberapa terhubung semangat ini dengan arak-arakan ekumenikal. Penulis menggunakan studi pustaka untuk menganalisisnya. Semangat pluralitas postmodern mempromosikan kembali prinsip gotong royong yang mengantarai kelompok Kristen untuk dialog berbasis relasi sosial dengan kelompok radikal. Untuk membangun hubungan dengan kelompok yang menjaga jarak dengan Kekristenan dibutuhkan pendekatan budaya yang melekat di antara keduanya dan spirit yang mempersatukan sebagai bangsa. Dengan begitu, dialog dengan kelompok radikal bukanlah sebuah keniscayaan melainkan kemungkinan untuk menjaga kebhinekaan.